ISLAMIC RELIGIOUS EDUCATION TEACHERS’ STRATEGIES IN SHAPING STUDENTS’ RELIGIOUS CHARACTER AT SMPIT INSAN - Qolbi, Aisyah Ainul; Salim, Hakimuddin (Pena Cendekia Insani, 2026)
This study examines Islamic Religious Education teachers’ strategies in shaping students’ religious character at SMPIT Insan Kamil Karanganyar. Strengthening religious character has become an important aspect of education in Islamic schools amid contemporary moral challenges faced by students. This study employed a descriptive qualitative field research design using observation, interviews, and literature review. The findings reveal that teachers implemented several strategies, including exemplary conduct, discipline, habituation, and special programs such as Bina Pribadi Islami (BPI) and Malam Bina Iman dan Taqwa (MABIT). Exemplary conduct emerged as the primary strategy because teachers function as role models for students. Supporting factors included collaboration among school members, a religious school culture, and effective teacher–student communication, while family-school inconsistency and limited instructional time became major obstacles. The study implies that successful religious character formation requires teacher strategies, supportive school culture, and active family involvement.